Severe Carpal Tunnel Syndrome Caused by Gouty Tophi Diagnosed by Dual Energy Computed Tomography: Case Report - Yan GE,; Fen LI,; Jinwei CHEN,; Jing TIAN, (Archives of Rheumatology, 2016)
Gout is a common form of inflammatory arthritis, and the majority of gout patients experience recurrent acute attacks, joint damage, and other complications. Carpal tunnel syndrome caused by gouty tophi indicates the severity of untreated gouty tophi. In this article, we report a 54-year- old male chronic gout patient with serious carpal tunnel syndrome secondary to monosodium urate crystal deposit. The patient was admitted to our department with palmar numbness and disability for two years. He had a history of gout for 30 years but received no treatment. Multiple monosodium urate crystals were observed to be deposited in and around carpal tunnel on the three-dimensional reconstruction using dual energy computed tomography, which confirmed the diagnosis. The needle biopsy and electrophysiological test also supported the diagnosis. Our case indicates that dual energy computed tomography is a useful method to diagnose carpal tunnel syndrome associated with gout and that we should keep in mind the possibility of gouty tophi as a possible cause of carpal tunnel syndrome.